Premieren '83 : 24 Kölner Galerien und die Museen der Stadt Köln. - Galerie Baecker, Köln; Baukunst-Galerie, Köln; Galerie Thomas Borgmann, Köln; Galerie Dreiseitel, Köln; Galerie Gugu Ernesto, Köln; Galerie Glöckner, Köln; Galerie Gmurzynska, Köln; Galerie Karsten Greve, Köln; Galerie Hermes, Köln; Galerie Holtmann, Köln; Galerie Rudolf Kicken, Köln; Galerie Koppelmann, Köln; et al. (Köln : Stadt Köln, 1983)
Santarossa, Hella ; Roda, Fernand ; Fussmann, Klaus ; Anderle, Jiri ; Vedova, Emilio ; Uecker, Günther ; Anzinger, Siegfried ; Seewald, Richard ; Delaunay, Robert ; Fontana, Lucio ; Wawrin, Isolde ; etc.
Premieren '83 : 24 Kölner Galerien und die Museen der Stadt Köln, 12. - 14.5.83
boek